Impact of fungal pretreatment on methane enhancement and microbiome dynamics in the anaerobic digestion of floral waste - Pandey K.P.; Dhoble A.S. (My University, 2025)
Flowers are used all over the world, but because of their low shelf life, they are usually discarded after one-time use. Despite the huge amount of waste generation, its management is scarce. This study explores the anaerobic digestion of floral waste and assesses the impact of fungal pretreatment on the process, which is very less explored. Floral waste pretreated with the fungus Trichoderma longibrachiatum produced methane peak on day 9, while in positive control, methane peak was reported on day 18. Till day 9, fungal-treated floral waste produced 168.37 % more methane than the positive control. By metagenomic analysis, the fungal pretreated sample was revealed to have higher microbial diversity, and it was observed to have a higher abundance of Clostridium and Bacteroides than the positive control. Consortium of Clostridium and Bacteroides are reported to enhance system performance. Thus, fungal pretreatment can be used as an economically viable way to improve the throughput of the process. © 2025 Elsevier Ltd